Single Level Proximal Thoracic Pedicle Subtraction Osteotomy for Fixed Hyperkyphotic Deformity: Surgical Technique and Patient Series. Issue 5 (22nd July 2017) - Obeid, Ibrahim; Diebo, Bassel G; Boissiere, Louis; Bourghli, Anouar; Cawley, Derek T; Larrieu, Daniel; Pointillart, Vincent; Challier, Vincent; Vital, Jean Marc; Lafage, Virginie
Abstract: BACKGROUND: Thoracic hyperkyphosis can display pathological deterioration, resulting in either hyperlordotic cervical compensation or sagittal malalignment. Various techniques have been described to treat fixed malalignment. Pedicle subtraction osteotomy (PSO) is commonly used in the lumbar spine and frequently limited to the distal thoracic spine. This series focuses on the surgical specificities of proximal thoracic PSO, with clinical and radiological outcomes. OBJECTIVE: To report the surgical specificities and assess the clinical and radiological outcomes of proximal thoracic osteotomies for correction of rigid kyphotic deformities. METHODS: This is a retrospective review of 10 consecutive patients who underwent single level proximal thoracic PSO (T2-T5). Preoperative and postoperative full-body EOS TM radiographs, perioperative data, and complications were recorded. The surgical technique and its nuances were described in detail. RESULTS: Patients had mean age of 41.8 yr and 50% were female. The technique provided correction of segmental and global kyphosis, 26.6° and 29.5°, respectively. Patients reported reciprocal reduction in C2-C7 cervical lordosis (37.6°-18.6°, P < .001), significantly correlating with the reduction of thoracic hyperkyphosis (R = 0.840, P = .002). Mean operative time was 291 min, blood loss 1650 mL, and mean hospital stay was 13.8 d. Three patients reported complications that were resolved, including 1 patient who was revised because of a painful cross link. There were no neurological complications, pseudarthroses, instrumentation breakage, or wound infections at a minimum of 2-yr follow-up. CONCLUSION: Proximal thoracic PSO can be a safe and effective technique to treat fixed proximal thoracic hyperkyphosis leading to kyphosis reduction and craniocervical relaxation.